Phosphate Rich Organic Manure (PROM) – A novel organic fertilizer - UDAWAT, PUSHPIKA (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted at School of Agricultural Sciences, Udaipur, during 2019–2021 to study the outcome of phosphorous rich organic manure in groundnut and wheat during rainy (kharif) and winter (rabi) cropping season on clay loamy soil. Four concentrations of phosphorous rich organic manure, viz. 1, 2 (optimal dose), 3, 4, and 5 kg/ha in addition to the optimum dose of nitrogen and potassium were applied in five replicates. Phosphorous rich organic manure treated and control field (without fertilizer) were considered for comparative study. Appreciably higher yield was observed for groundnut under treatment 3, 4, and 5 over control in all the five replicates. The residual effect of phosphorous rich organic manure was observed in the subsequent wheat crop, as evident with higher phosphorous uptake in comparison to the control field. All the phosphorous rich organic manure treated fields produced noticeably higher grain, tiller number, spike length and straw yield of wheat in comparison to the control field. Therefore, phosphorous rich organic manure has been a proven alternative source of organic phosphorous fertilizer in comparison to other chemical based fertilizers that has several harmful effects on soil, environment, and water resources and also to the plant itself. Hence, time has come to replace chemical based phosphorous fertilizers with organic phosphorous fertilizer which is eco-friendly with low cost fertilization and having residual effect on the subsequent crops as well.